Pairing-Based Cryptography - Pairing 2008 Second International Conference, Egham, UK, September 1-3, 2008, Proceedings - Galbraith, Steven; Paterson, Kenny (Security and Cryptology ;, 2008)
This book constitutes the thoroughly refereed proceedings of the Second International Conference on Pairing-Based Cryptography, Pairing 2008, held in London, UK, in September 2008. The 20 full papers, presented together with the contributions resulting from 3 invited talks, were carefully reviewed and selected from 50 submissions. The contents are organized in topical sections on cryptography, mathematics, constructing pairing-friendly curves, implementation of pairings, and hardware implementation.